Exploration of the Role Play Method in Improving Student’s Speaking Skills In Klaten - Fitriani, Rizki; Susiati, Susiati (Journal of English Language and Education, 2025)
This study explores the the role play method in improving english speaking skills in junior high school. The background of study is the low level of students’ english speaking skills, which is due to the lack of practice and low self-confidence. The main objective in this study is to decribes the role play method in improving english speaking skills at the junior high school level. The method used in the research is descriptive qualitative approach, with data collection obtained through interviews and observations. The findings highlight student barriers, the importance of real practice and the adjusment of curriculum materials. The results showed that the application of the role play method had students’ involvement in learning and this method proved to very effective in improving students’ fluency and accuracy in learning the language. This research is expected to contribute to more creative users of the role play method at junior high school level.